Determining female-specific high-intensity activity GPS thresholds in women's rugby union: Use of current use of male-derived absolute speed thresholds underestimates true levels - Bradley, E.; Roberts, J.; Archer, D. (European Journal of Sport Science, 2025)
GPS speed thresholds in women's rugby union are usually based on data derived from the men's game. However, evidence suggests the maximum speeds achieved by female players are 2-8 km.h-1 slower and the volume of high-intensity running (HIR) in women's rugby may be underestimated. The aim of the study was to examine the effect of adjusting absolute thresholds on the volume of high-intensity locomotion. GPS units recorded movement data from 58 players across 18 English Premier15 s matches. Distance in HIR and sprint (Spr) zones were calculated using male-derived criteria: AbsMale (HIR >18 km.h-1; Spr =21 km.h-1). Two alternative thresholds were compared: AbsFVmax (HIR >16 km.h-1; Spr =19 km.h-1); AbsFemale (HIR >14 km.h-1; Spr =17 km.h-1). Data were analysed using one-way ANOVA and effect sizes to determine differences in distances between thresholds. AbsMale HIR and Spr distances were 63 ± 71 m and 30 ± 53 m. Significantly greater distances at higher-intensity speeds were observed with female-adjusted thresholds. AbsFVmax: HIR: 139 ± 116 m (p = 0.01, ES 0.80); Spr: 60 ± 90 m (p = 0.131, ES 0.41) and AbsFemale: HIR: 239 ± 157 m (p < 0.01, ES 1.45); Spr: 137 ± 152 m (p < 0.01, ES 0.94). 24 players (41%) achieved speeds greater than the 21 km·h-1 threshold with the male-derived thresholds. At AbsFVmax threshold this increased to 44 (76%) and 100% at the AbsFemale threshold. Existing male-derived thresholds appear to underestimate high-intensity locomotion of female players. With adjusted thresholds, specifically the AbsFemale, the proportional volume of high-intensity activity in the women's game (8.2% total distance) aligns more closely to that observed during men's match-play.